PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATERI KESEIMBANGAN BENDA TEGAR SISWA KELAS XI IPA 5 SMA N 3 DEMAK SEMESTER 2 TAHUN PELAJARAN 2013/2014 - Mustaqimah . (Universitas PGRI Semarang, 2015)
The formulation of the problem of this research was how much improvement of the students?óÔé¼Ôäó activity and learning outcomes, and the change of the students?óÔé¼Ôäó behavior by using Project Based Learning Model for the students of Class XI IPA 5 of SMA Negeri 3 Demak. This PTK was done in two cycles. There was a changing in learning behavior from the students?óÔé¼Ôäó enthusiasm in learning, the interaction between the students and the teacher, the interaction between the students themselves, the teamwork, the students?óÔé¼Ôäó activity in group discussion, the students?óÔé¼Ôäó efforts in following the learning process, and the students?óÔé¼Ôäó participation in concluding the learning material. The result of cycle 1 was 28 (65,12 %) of the students completed the learning process, and 15 (34,88 %) did not complete the learning process. The class average was 71,74 in cycle 1 and increased to 81,35 in cycle 2. Keywords: project based learning method, learning activity, learning achievement.